Cytogenetic characterization of six species of flatfishes with comments to karyotype differentiation patterns in Pleuronectiformes (Teleostei) - Azevedo, M. F. C.; Oliveira, C.; Pardo, B. G.; Martinez, P.; Foresti, F. (Blackwell Publishing, 2007)
The karyotypes and cytogenetic characteristics of flatfishes species Paralichthys orbignyanus, Paralichthys patagonicus, Citarichthys spilopterus and Etropus crossotus (Paralichthyidae), Bothus ocellatus (Bothidae) and Symphurus tessellatus (Cynoglossidae) were investigated by conventional [Giemsa staining, C-banding, Ag- and chromomycin (CMA(3))-stainings] and molecular [in situ hybridization (ISH)] cytogenetic techniques. The results showed 2n = 46 and FN = 48 (2msm + 46sta) in P. orbignyanus, 2n = 46 and FN = 46 (46sta) in P. patagonicus, 2n = 26 and FN = 44 (18msm + 8sta) in C. spilopterus, 2n = 38 and FN = 64 (26msm + 12sta) in E. crossotus, 2n = 32 and FN = 50 (18msm + 14sta) in B. ocellatus, and 2n = 46 and FN = 62 (46msm + 62sta) in S. tessellatus. All species exhibited weak C-band positive segments in terminal and centromeric positions of some chromosome pairs. Silver staining of the nucleolus organizer regions (Ag-NOR) technique showed a single Ag-NOR-bearing chromosome pair in all species except E. crossotus. All these sites were CMA(3) positive and showed clear ISH signals after probing with a 18S rRNA probe. Etropus crossotus presented until seven chromosomes with Ag-NORs and CMA(3) positively stained segments in five chromosome pairs. Conversely only one chromosome pair was identified with the ISH experiments in this species. The available results show that the fishes of the order Pleuronectiformes experienced a marked chromosome evolution that included reduction in diploid number, mainly due to Robertsonian rearrangements, and several chromosome inversions. (c) 2007 the Authors Journal compilation (c) 2007 the Fisheries Society of the British Isles.
Keywords: chromosome banding; cytotaxonomy of flatfishes; in situ hybridization (ISH); karyotype; NOR phenotype